BRICK LANE: MIRRORING NAZNEEN’S METAMORPHOSIS - Hossain Al Mamun (European Scientific Journal, ESJ, 2014)
Brick Lane (2003) unfolds a story of an immigrant woman—Nazneen, and her journey to Britain from Bangladesh and her all out strugle for getting freedom. Heraclitus comments in the beginning of the novel—“A man’s character is his fate”, but the story presents man’s supremacy over his fate. Nazneen falls in bad condition so many times, but her inner strength fights against her fate which gradually develops and this study compares that change with butterfly’s metamorphosis. Like a moth of a butterfly Nazneen comes out from an exoskeleton of social barriers and gets true color of her wings. This study intends to present what are the social barriers in these two countries, how and by whom Nazneen was influenced to fight against those obstacles, which way she reflects as a new one and what is the outcome of that reflection.